The Impact of Coal Quality and Availability on the Efficiency of Distribution Strategies: A Perspective from the Polish Mining Sector - Kornelia PRZEDWORSKA (Communications of International Proceedings, 2025)
This study investigates how coal quality and availability influence the efficiency of distribution strategies in the Polish mining sector—an issue that gained urgency following the energy crisis triggered by the war in Ukraine. Despite extensive literature on supply chain management, research on declining markets and the impact of raw material characteristics on distribution remains scarce. The study addresses this gap through qualitative research based on semi-structured, in-depth interviews with senior managers from all eight operational Polish coal mining companies. Thematic and emergent coding techniques were applied to analyze the data using Creswell’s methodology. The findings reveal that coal quality directly affects customer satisfaction and the perceived efficiency of distribution strategies, while availability constraints shape inventory practices and the resilience of supply chains. Mining firms demonstrate limited flexibility in adjusting production volumes, which is constrained by geological, regulatory, and labor-related factors. Four distinct surplus stock management strategies were identified, ranging from speculative storage to external warehousing. Moreover, the role of intermediaries proved vital in customizing coal products to meet end-user requirements, thus enhancing adaptability and market fit. This research contributes to strategic management in resource-based and declining industries, offering practical implications for production planning, inventory optimization, and stakeholder coordination. It recommends improving product alignment with market needs, leveraging intermediaries’ capabilities, and developing adaptive strategies to cope with resource constraints and market volatility. The study enhances our understanding of supply chain efficiency under structural limitations and provides a foundation for further research in energy and distribution economics.
Keywords: Coal distribution strategies; Resource availability; Customer satisfaction; Supply chain management